PENGARUH PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN - Sisilia Imaculata Seku; Struce Andriyani (Universitas Nusa Cendana, 2023)
This study aims to explain employee perceptions about career development and employee performance and to analyze the effect of career development on employee performance at PT. Pegadaian Persero Ende Branch. The sample in this study were employees of PT. Pegadaian Persero Ende Branch as many as 75 people. The data analysis technique is simple linear regression analysis, descriptive analysis, t-test, and determination test. The results of the study suggest that Career Development at PT. Pegadaian Persero Branch Ende is in the very good category while the Employee Performance of PT. Pegadaian Persero Branch Ende is in the very good category. Career Development has a positive and significant effect on Employee Performance at PT. Pegadaian Persero Branch Ende.Thus, the company needs to maintain and improve the Career Development provided to its employees so that employees are more effective in carrying out their work. If the career development provided for employees is getting better, the employees will be better at completing work so employee performance will be good. Keywords: Career Development; Employee Performance; Employee Perceptions